Gestão escolar democrática à luz de Gramsci: uma análise da gestão escolar paulista - Santos, Gislaine Gonçalves dos (2022)
this dissertation presents the results of a research on democratic school management, which was investigated taking Gramsci's legacy as a theoretical reference, particularly the concept of unitary school formulated by him. The objective was to know the principles, purposes and methods of the current São Paulo school management, comparing it with what is possible to infer from what the Italian revolutionary communist formulated for the unitary school. So, the research problem was to verify which are the proximities and distances that are possible to be observed in the two investigated processes/management formulations. Through the method of bibliographic and documentary research, with a qualitative bias, texts by Gramsci and some commentators of the work he left were analyzed, as well as legislation and documents related to democratic school management, its historical development in Brazil and in the State of São Paulo. The main result achieved with the investigation was to verify that the two management perspectives investigated do not match, since the proposal by Gramsci aims at the emancipation of educational subjects and the one implemented in the State of São Paulo tries to adapt them to the needs of the social class. dominant from an economic and ethical and political point of view.